Pilihan Konsumsi Masyarakat Surabaya di Masa Pandemi Covid-19 - Muhammad Rizqi Bahrul Amin; Lucky Rachmawati (Universitas Negeri Surabaya, 2021)
This research was conducted in order to find out the consumption choices of surabaya people affected by the covid-19 pandemic in determining the most priority needs and what factors influence consumption choices in the midst of the covid-19 pandemic. Technical data collection from this study is by disseminating questionnaires to respondents, while the data analysis technique of this study uses descriptive analysis to process quantitative data. In conclusion, researchers draw the conclusion that the pandemic has a big impact on the economy of the people of Surabaya, especially related to the decrease in income, purchases in large quantities and scaling priorities in times of crisis, while the needs that become a priority is the Internet, Fresh food, medicines, hygienic personal needs & hygiene products, as well as communication needs, as for the main factors of consideration of the People of Surabaya is environmental factors namely the pandemic crisis covid-19, affordable prices, economic conditions of the community, easy distribution, quality products / services.